Principles of Immunopharmacology - Nijkamp, Frans P.; Parnham, Michael J.; SpringerLink (Online service) (Basel : Birkhäuser Basel, 2005)
This single volume represents an additional text for students who require background information on the immune response, its diagnosis and its modification by drugs and chemicals. The first section of the book, providing a basic introduction to immunology and its relevance for human disease, has been updated to accommodate new immunological concepts. The second section on immunodiagnostics has been further expanded to describe widely used molecular techniques and is followed by a systematic coverage of drugs affecting the immune system, revised to cover recent developments. The book concludes with a chapter on immunotoxicology. This second edition, thus, continues the unique format, dealing with four related topics in a single volume, obviating the need to refer to several different textbooks. New aids to readers include a two-column format, glossaries of technical terms and an appendix of reference tables. The emphasis on illustrations from the first edition is maintained. The book, written by international experts, is suitable as a course textbook for students of various biomedical, chemical and pharmaceutical sciences and as a supporting text for medical and postgraduate students.
Mechanisms of immunity -- Hematopoiesis, including lymphocyte development and maturation -- T cell-mediated immunity -- Antibody diversity and B cell-mediated immunity -- Cytokines -- Innate immunity phagocytes, natural killer cells and the complement system -- Inflammatory mediators and intracellular signalling -- Immune response in human pathology: infections caused by bacteria, viruses, fungi, and parasites -- Immune response in human pathology: hypersensitivity and autoimmunity -- Cancer immunity -- Neuroimmunoendocrinology -- Immunodiagnosis -- Antibody detection -- Immunoassays -- Flow cytometry -- Gene arrays -- Proteomics and applications within the drug development pipeline -- Immunotherapeutics -- Vaccines -- Sera and immunoglobulins -- Anti-allergic drugs -- Drugs for the treatment of asthma and COPD -- Immunostimulants in cancer therapy -- Anti-infective activity of immunomodulators -- Mild plant and dietary immunomodulators -- Influence of antibacterial drugs on the immune system -- Immunosuppressives in transplant rejection -- Cytotoxic drugs -- Corticosteroids -- Non-steroidal anti-inflammatory drugs -- Disease-modifying anti-rheumatic drugs -- Perspectives of immunotherapy in the management of asthma and other allergic conditions -- Immunotoxicology -- Immunotoxicology.
Keywords: Medicine; Immunology; Pharmacology; Allergy; Infectious diseases; Medical biochemistry; Cell biology; Biomedicine; Immunology; Pharmacology/Toxicology.; Cell Biology; Infectious Diseases; Allergology; Medical Biochemistry; Electronic books